Identification of pathogens and virulence profile of Rhodococcus equi and Escherichia coli strains obtained from sand of parks - Fernandes, M. C. [UNESP]; Takai, S.; Leite, D. S.; Pinto, José Paes de Almeida Nogueira [UNESP]; Brandao, P. E.; Santarem, V. A.; Listoni, F. J. P. [UNESP]; Da Silva, A. V.; Ribeiro, Márcio Garcia [UNESP] (Soc Brasileira Microbiologia, 2013)
The identification of pathogens of viral (Rotavirus, Coronavirus), parasitic (Toxocara spp.) and bacterial (Escherichia coli, Salmonella spp., Rhodococcus equi) origin shed in feces, and the virulence profile of R. equi and E. coli isolates were investigated in 200 samples of sand obtained from 40 parks, located in central region of state of Sao Paulo, Brazil, using different diagnostic methods. From 200 samples analyzed, 23 (11.5%) strains of R. equi were isolated. None of the R. equi isolates showed a virulent (vapA gene) or intermediately virulent (vapB gene) profiles. Sixty-three (31.5%) strains of E. coli were identified. The following genes encoding virulence factors were identified in E. coli: eae, bfp, saa, iucD, papGI, sfa and hly. Phylogenetic classification showed that 63 E. coli isolates belonged to groups B1 (52.4%), A (25.4%) and B2 (22.2%). No E. coli serotype O157:H7 was identified. Eggs of Toxocara sp. were found in three parks and genetic material of bovine Coronavirus was identified in one sample of one park. No Salmonella spp. and Rotavirus isolates were identified in the samples of sand. The presence of R. equi, Toxocara sp, bovine Coronavirus and virulent E. coli isolates in the environment of parks indicates that the sanitary conditions of the sand should be improved in order to reduce the risks of fecal transmission of pathogens of zoonotic potential to humans in these places.
Keywords: enteric pathogens; virulence; sand; feces; parks; E. coli; R. equi